Elevated Apoptosis and Impaired Proliferation Contribute to Downregulated Peripheral γδ T Cells in Patients with Systemic Lupus Erythematosus - Zhimin Lu; Dinglei Su; Dandan Wang; Xia Li; Xuebing Feng; Lingyun Sun (Clinical and Developmental Immunology)
Objective. To investigate the frequency of peripheral γδ T cells in patients with systemic lupus erythematosus (SLE) and its correlation with disease activity and to analyze the apoptotic status, proliferation ability, and intracellular cytokine profile of these cells. Methods. Flow cytometry was performed to detect the percentage and intracellular cytokine expression of peripheral γδ T cells from SLE patients. Annexin-V/PI double staining was applied to determine the proportion of apoptotic γδ and CD3+ T cells. γδ T cell proliferation was analyzed by CFSE labeling technique. Results. The percentage and absolute number of γδ T cells were remarkably decreased in active SLE patients compared to those in inactive patients and healthy controls, with γδ T cell count negatively correlated with disease activity. Compared with healthy controls, peripheral γδ T cells from active SLE patients exhibited higher apoptotic rate and lower proliferation ability, as well as elevated expression of intracellular IFN-γ, IL-4, IL-10, and TGF-β, but not IL-17 or Foxp3. Conclusion. Decreased γδ T cells in the peripheral blood of SLE patients might be caused by upregulated apoptosis and downregulated cell proliferation. These γδ T cells may secret both pro- and anti-inflammatory cytokines to perform their functions in SLE.